Pemanfaatan Media Sosial Instagram sebagai Sarana Promosi TXTURE - Muhammad Rifqi Fakhruddin; Yulianti (Bandung Conference Series: Communication Management, 2023)
Abstract. The current business development makes several sectors in the fashion industry increase. Especially social media has an important role in making it easier for business people to promote and sell sales. One of the platforms described in this study is instagram, instagram is a platform that has a wide and large reach. as did the TXTURE brand where they use instagram as one of the promotional media by bringing out the uniqueness of the TXTURE brand. The purpose of this study is to determine the form of promotion, and to find out what factors are an obstacle for TXTURE. This study uses a qualitative research method with a case study approach formulated by Robert K Yin, where the method examines a case using the main questions "how" and "why". The data obtained in this study is the result of interviews with Prima Rahadiantara who are social media managers and owners of TXTURE Shoe and Bootmaker. the researcher tries to uncover the form of TXTURE promotion, the urgency of the dollar as a transaction currency and promotional barriers as well as solutions to these obstacles. TXTURE uses Instagram by considering the time span, upload consistency and variety of promotions is a service provided by TXTURE as a form of promotion. Dollars are also used as currency for TXTURE product transactions as an internationalization effort. The social media manager for the TXTURE Instagram account is the main obstacle for TXTURE, because the promotion or content management is handled directly by the owner so that sometimes it becomes an obstacle in carrying out promotions. However, these obstacles have not reduced TXTURE's promotion on Instagram media, because to minimize these things, TXTURE organizes events and festivals. Abstrak. Perkembangan bisnis saat ini membuat beberapa sektor dalam bidang industri fashion semakin meningkat. Salah satu platform yang dijelaskan dalam penelitian ini yaitu instagram, instagram merupakan platform yang jangkauannya luas dan besar. sebagaimana yang dilakukan oleh brand TXTURE dimana mereka menggunakan instagram sebagai salah satu media promosi dengan memunculkan keunikan dari brand TXTURE. Tujuan dari penelitian ini yaitu untuk mengetahui bentuk promosi, dan untuk mengetahui faktor apa saja yang menjadi hambatan bagi TXTURE. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus yang dirumuskan oleh Robert K Yin, dimana metode ini mengkaji suatu kasus dengan menggunakan pertanyaan utama “bagaimana” dan “mengapa”. Data yang diperoleh dalam penelitian ini merupakan hasil dari observasi dan melakukan wawancara dengan Prima Rahadiantara yang menjabat sebagai pengelola media sosial sekaligus pemilik dari TXTURE Shoe and Bootmaker. Peneliti berusaha untuk mengungkap bentuk promosi TXTURE, urgensi dollar sebagai mata uang transaksi dan hambatan promosi serta solusi dari hambatan tersebut. TXTURE menggunakan Instagram dengan mempertimbangkan rentang waktu, konsistensi unggahan dan variasi promosi merupakan pelayanan yang diberikan TXTURE sebagai bentuk promosi. Dollar pun digunakan sebagai mata uang transaksi produk TXTURE sebagai upaya internasionalisasi. Pengelola media sosial akun instagram TXTURE menjadi hambatan utama TXTURE, dikarenakan pengelolaan promosi atau konten ditangani langsung oleh pihak pemilik sehingga hal tersebut terkadang menjadi suatu hambatan dalam pelaksanaan promosi. Akan tetapi, hambatan tersebut tidak membuat promosi TXTURE pada media Instagram menurun, kerena untuk meminimalisir hal tersbut TXTURE melakukan event dan festival.